Retinoic acid catabolizing enzyme CYP26C1 is a genetic modifier in SHOX deficiency. Issue 12 (14th November 2016) - Montalbano, Antonino; Juergensen, Lonny; Roeth, Ralph; Weiss, Birgit; Fukami, Maki; Fricke‐Otto, Susanne; Binder, Gerhard; Ogata, Tsutomu; Decker, Eva; Nuernberg, Gudrun; Hassel, David; Rappold, Gudrun A
Abstract: Mutations in the homeobox gene SHOX cause SHOX deficiency, a condition with clinical manifestations ranging from short stature without dysmorphic signs to severe mesomelic skeletal dysplasia. In rare cases, individuals with SHOX deficiency are asymptomatic. To elucidate the factors that modify disease severity/penetrance, we studied a three‐generation family with SHOX deficiency. The variant p.Phe508Cys of the retinoic acid catabolizing enzyme CYP26C1 co‐segregated with the SHOX variant p.Val161Ala in the affected individuals, while the SHOX mutant alone was present in asymptomatic individuals. Two further cases with SHOX deficiency and damaging CYP26C1 variants were identified in a cohort of 68 individuals with LWD. The identified CYP26C1 variants affected its catabolic activity, leading to an increased level of retinoic acid. High levels of retinoic acid significantly decrease SHOX expression in human primary chondrocytes and zebrafish embryos. Individual morpholino knockdown of either gene shortens the pectoral fins, whereas depletion of both genes leads to a more severe phenotype. Together, our findings describe CYP26C1 as the first genetic modifier for SHOX deficiency. Synopsis: SHOX mutations lead to SHOX deficiency, a disorder mostly characterized by isolated short stature and skeletal dysplasia. Co‐occurrence of CYP26C1 and SHOX mutations in patients and CYP26C1 loss in zebrafish experiments support a role for CYP26C1 variants in SHOX genotype modulation. Damaging mutations in SHOX and the retinoic acid‐degrading enzyme CYP26C1 co‐occur in severely affected SHOX deficiency individuals. CYP26C1 is expressed in primary chondrocytes and zebrafish embryos pectoral fins, suggesting that it may regulate retinoic acid levels during limb development. Loss of CYP26C1 in zebrafish embryos leads to increased retinoic levels, reduced SHOX expression, and shortened pectoral fins. CYP26C1 acts as genetic modifier of SHOX deficiency by regulating retinoic acid intracellular levels upstream of SHOX in the retinoic acid signalling pathway. Retinoic acid represents the most active biological form of vitamin A. Manipulating vitamin A metabolism in SHOX deficiency patients may alleviate the skeletal abnormalities of this condition. Abstract : SHOX mutations lead to SHOX deficiency, a disorder mostly characterized by isolated short stature and skeletal dysplasia. Co‐occurrence of CYP26C1 and SHOX mutations in patients and CYP26C1 loss in zebrafish experiments support a role for CYP26C1 variants in SHOX genotype modulation.